Analisis Aspek Akuntabilitas Pengelolaan Dana Haji Melalui Aplikasi SISKOHAT - Muhammad Nugraha Eka Wardana; Dwi Suhartini (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Based on data from the Hajj Financial Management Agency (BPKH), the total hajj funds up to December 2020 is 145.7 T rupiah. The amount of funds that are not small certainly requires good management by the Ministry of Religion. However, the facts on the ground are that corruption and funding of hajj funds are still going on, which has resulted in many people questioning the accountability of the management of these hajj funds. On the other hand, the Ministry of Religion is also trying to make improvements, one form of effort in bridging information to the public is maximizing the use of the Integrated Hajj Information and Computerization System (SISKOHAT). Through this research, we want to explore how the implementation and the impact caused by SISKOHAT will be. This study uses a qualitative method with a phenomenological approach to correlate the data obtained. This method is used to examine the condition of the problem of Hajj funds naturally and more deeply through various Hajj phenomena. Specifically, the research was conducted by collecting data along with observations. The research location is the Ministry of Religion of Blitar City, where the researchers chose this location because Blitar City is one of the "City" category areas that has a long waiting list for departures in East Java, so many prospective Hajj pilgrims (CJH) need information on Hajj. In the review of the literature point of view, the researcher will also discuss the perspective of stakeholder theory in the phenomenon of this Hajj fund information. The results showed that the implementation of SISKOHAT in the Ministry of Religion of Blitar City could be successful through 3 main indicators, namely the application of SISKOHAT Gen 3 has been implemented in all, the sophistication system and experts have been in accordance with applicable policies. aspects of local government accountability.